Assessment of basal heave for wide excavations using the finite element method - Tan, Christina Ai Wei. (2013)
Braced excavation is gaining popularity as a construction method. To design an excavation safely, designers must have a good knowledge of the behavior of excavations, especially bottom basal heave. Besides, they should also know the limitations of using conventional methods and finite element methods to obtain the factor of safety.